(untitled) (Research, Society and Development, 2022)
Objective: Identify possible genetic and epigenetic factors associated with the development of adult T-cell leukemia/lymphoma. Methodology: This is a work based on the integrative review of the literature. The search for articles was performed using the descriptors indexed in the DeCS (Descriptors in Health Sciences) and MeSH (Medical Subject Headings), articles published in the last 5 years were included. Results and Discussion: The carcinogenesis process that culminates in the progression of ATLL has several phases over a long period of time. The beginning of the neoplastic process is related to the expression of viral oncoprotein Tax, which induces replication and initiation of the clonal expansion process. HBZ oncoprotein and HBZ RNA are continuously transcribed into neoplastic cells and influence the process of cell proliferation and viral persistence. In addition to genetic factors that are generally mediated by Tax and HBZ proteins, epigenetic changes are also required, such as histone acetylation and DNA methylation. Conclusion: it is then concluded that genetic factors such as Tax, HBZ, FYN, PLCG1, CD247, DLG1, VAV1, ERC1, PRKCQ, CARD11, RELA, IKBKB, TET1, TET2, MLL2, MLL3 DNMT1 e IRF4. And epigenetic pathways that act on DNA methylation and histone acetylation are involved in the HTLV-1-mediated carcinogenesis process.